Comparison of Oxidant-Antioxidant Status in Patients with Vitiligo and Healthy Population - Agrawal, S; Kumar, A; Dhali, TK; Majhi, SK (Kathmandu University Medical Journal, 2015)
Background Vitiligo is a well-recognized pigmentary disorder of the skin and /or mucous membrane characterized by circumscribed ivory or chalky white macules devoid of identifiable melanocytes. The pathogenesis of vitiligo is complex and still not well understood. According to autocytotoxic hypothesis, oxidative stress has been suggested to be the initial pathogenic event in melanocyte degeneration. The role of free radicals and oxidative damage in the pathophysiology of vitiligo has been documented in recent studies. Objective To evaluate the role of oxidative stress in patients with vitiligo and of healthy controls by measuring levels of the oxidant malondialdehyde (MDA) and antioxidants vitamin C and vitamin E in serum and catalase (CAT) in erythrocytes. Method A total of 80 clinically diagnosed cases of vitiligo and 80 control subjects were included in the study to assess the activity of MDA, vitamin C and vitamin E in serum and CAT in erythrocytes of patients and controls by using the spectrophotometric assay. Result There was statistically significant increase in the levels of MDA in patients with vitiligo compared to the control group (p<0.001). No significant difference was found in the levels of vitamin C (p=0.411) and vitamin E (p=0.771) between the patients with vitiligo and control group. The levels of CAT in the vitiligo patients were found to be significantly lower than those of controls (p<0.001). Conclusion Increased oxidative stress and decreased catalase have been observed in vitiligo patients and the data suggesting that the free radicals may be involved in the destruction of melanocytes or dysregulation of melanogenesis. Kathmandu University Medical Journal Vol.12(2) 2014: 132-136